Deterrence by insurgents: Hezbollah's military doctrine and capability vis-à-vis Israel. (18th August 2022) - Al-Aloosy, Massaab
ABSTRACT: Deterrence between states is a long-established theory in security studies, but it is rare, if not unique, that an insurgency would deter a state from attacking another country. Insurgencies in the Middle East are increasingly playing an international role, of which deterrence is only a part. This generates an interesting dynamic in which an insurgency uses non-traditional tools to dissuade an adversarial state from attacking the group or country in which it resides. Thus, the research topic is: How is Hezbollah able to deter Israel?